Dying for an iPhone : Apple, Foxconn, and the lives of China's workers - Chan, Jenny (Jenny Wai-ling); Pun, Ngai, 1970-; Selden, Mark (Chicago, Illinois Haymarket Books, 2020)
"A harrowing look at the lives and struggles of a new generation of Chinese workers confronting the Apple-Foxconn empire and the Chinese state. Suicides, excessive overtime, and hostility and violence on the factory floor in China. Drawing on vivid testimonies from rural migrant workers, student interns, managers and trade union staff, Dying for an iPhone is a devastating expose of two of the world's most powerful companies: Foxconn and Apple. As the leading manufacturer of iPhones, iPads, and Kindles, and employing one million workers in China alone, Taiwanese-invested Foxconn's drive to dominate global electronics manufacturing has aligned perfectly with China's goal of becoming the world leader in technology. This book reveals the human cost of that ambition and what our demands for the newest and best technology means for workers. Foxconn workers have repeatedly demonstrated their power to strike at key nodes of transnational production, challenge management and the Chinese state, and confront global tech behemoths. Dying for an iPhone allows us to assess the impact of global capitalism's deepening crisis on workers."--Publisher's website
1. A Suicide Survivor -- 2. Foxconn: The World's Largest Electronics Manufacturer -- 3. Apple Meets Foxconn -- 4. Managing Foxconn -- 5. Voices of Student Interns -- 6. Fire and Brimstone -- 7. Wandering the City -- 8. Chasing Dreams -- 9. Confronting Environmental Crisis -- 10. Dead Man Walking -- 11. Strikes and Protests -- 12. Apple, Foxconn, and the Lives of China's Workers -- Epilogue -- Appendix 1: Our Book Website -- Appendix 2: Suicides and Attempted Suicides at Foxconn in China, 2010 -- Appendix 3: Fieldwork in China -- Appendix 4: Foxconn Facilities Around the World.
Includes bibliographical references (pages 251-264) and index.
110257
Keywords: Foxconn International Holdings Ltd. -- Employees; Apple Computer, Inc. -- Employees; Apple Computer, Inc; Foxconn International Holdings Ltd; Work environment -- China; Quality of work life -- China; Political Science -- Labor & Industrial Relations; Employees; Quality of work life; Work environment; China